Alluvial architecture of mid‐channel fluvial–tidal barforms: The mesotidal Lower Columbia River, Oregon/Washington, USA. Issue 7 (21st July 2020) - Prokocki, Eric W.; Best, James L.; Ashworth, Philip J.; Sambrook Smith, Gregory H.; Nicholas, Andrew P.; Parsons, Daniel R.; Simpson, Christopher J.
Abstract: Barforms of mesotidal to macrotidal fluvial–tidal transitions, regardless of fluvial‐discharge, are currently thought to display a sedimentary architecture dominated by tidal signatures. Due to the scarcity of observations from modern mesotidal fluvial–tidal transitions, especially those of multi‐channelled large‐rivers (mean annual discharge ≥7000 m 3 s −1 and peak discharges ≥15 000 m 3 s −1 ) with mid‐channel bars, this concept remains unproven. The present study analyses data produced by a combination of high‐resolution ground penetrating radar and coupled shallow vibracores (<5 m depth), collected from modern fluvial–tidal mid‐channel bars of the mesotidal multi‐channelled Lower Columbia River, Washington/Oregon, USA, which can experience peak discharges ≥18 000 m 3 s −1 . These data were used alongside time‐sequenced aerial imagery to characterize the spatio‐temporal sedimentological evolution of these barforms in singular flows or combined flows consisting of river, tidal and/or wind‐wave oscillatory, current components operating in unique fluvial–tidal transition regimes. Results indicate that ca 75% of the Lower Columbia River fluvial–tidal transition produces braid‐bars with basal to bar‐top sedimentological architectures that are indistinguishable from fluvial‐only braid‐bars recorded in the literature. Barform stratal characteristics within the fluvial–tidal transitions of mesotidal large‐rivers are therefore more likely to be dominated by downstream‐oriented currents. Furthermore, a new style of low‐angle (<5°) inclined heterolithic stratification found in bar‐top accretion‐sets within upper‐mixed tidal–fluvial regime braid‐bars is observed. This common stratification is created by combined‐flows characterized by intrabasinal wind‐wave oscillatory‐currents and bidirectional tidal‐currents. This inclined heterolithic stratification marks the initial downstream fluvial–tidal crossover point from Lower Columbia River up‐dip fully‐fluvial braid‐bar architectures, to those possessing bar‐top facies produced by the hydraulic‐sedimentation response of combined intrabasinal wind‐wave and tidal influence. When preserved, this form of mid‐channel bar inclined heterolithic stratification provides a unique sedimentological signature of multi‐channelled fluvial–tidal transitions that possess an open‐water lower basin with intrabasinal wind‐waves.